EXECUTIVE SKILLS AFFECTING THE ACADEMIC ADMINISTRATION OF THE SCHOOL UNDER THE DEPARTMENT OF LOCAL ADMINISTRATION LOPBURI PROVINCE - Yodrayab, Nittaya; Dejbamrung, Somchai; Dejbamrung, Sombat; Surasakhon, Wirot; Jummuang, Jamjuree (Journal of MCU Nakhondhat, 2024)
The purposes of this research were to: 1) assess the executive skills of the schools under the Department of Local Administration Lopburi Province, 2) evaluate the academic administration of the schools under the Department of Local Administration Lopburi Province and 3) determine the affecting between the executive skills and the academic administration of the school under the Department of Local Administration Lopburi Province. The sample size was determined using Krejcie and Morgan’s table, resulting in a sample of 226 teachers. Stratified sampling was employed to select the participants. The research instrument was structured interview and 5-point Likert scale questionnaire consisting of three parts: 1) general information of respondents, 2) the executive skills of the schools under the Department of Local Administration Lopburi Province. and 3) the academic administration of the schools under the Department of Local Administration Lopburi Province. Data analysis methods included frequency, percentage, arithmetic mean, standard deviation, and stepwise multiple regression analysis. The research findings that: 1) the executive skills of the schools under the Department of Local Administration Lopburi Province were overall at a high level, When considering each aspect, it was found that they were at a high level in all aspects, highest average was in the human relations, followed by the concept, and the lowest was the technical methods; 2) the academic administration of schools under the Department of Local Administration Lopburi Province were overall at a high level. When considering each aspect, it was found that the aspect with the highest average was the aspect of promoting student morality and ethics followed by the measurement and evaluation, and the lowest is library work and 3) a statistically significant affecting was found between the executive skills and the academic administration of schools under the Department of Local Administration Lopburi Province at the .01 level of significance